PENGARUH PENGEMBANGAN KARIR DAN DISIPLIN KERJA TERHADAP KINERJA GURU SMK NEGERI SE-KOTA BIMA DENGAN MOTIVASI KERJA SEBAGAI INTERVENING - Zulbahri Zulbahri; I Nyoman Nugraha Ardana Putra; Heriani Heriani (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to analyze the influence of career development and work discipline on the performance of SMKN teachers in Bima city with work motivation as an intermediary variable. The method used in this study is quantitative. The number of research resondents was 68 people who were selected proportionally sampling with a total population of 217 teachers at SMKN in Bima city. Data collection method using questionnaires. Data analysis techniques using SmartPLS 3. The results of the research obtained: Career development, Work Discipline, and Work Motivation have a positive and significant effect on the performance of SMKN teachers in the city of Bima, and Motivation is able to mediate career development, Work Discipline has a positive and significant effect on the performance of SMKN teachers in the city of Bima.